Pengembangan kompetensi digital Bengkalis UMKM community di Kabupaten Bengkalis - Belli Nasution; Nita Rimayanti; Anuar Rasyid; Afrianto Daud; Anita Mediana (Unri Conference Series: Community Engagement, 2021)
The Covid-19 pandemic has had a major impact on MSME players, especially in the Bengkalis area. Bengkalis is an archipelago which is a strategic place to promote MSME products to other countries such as Malaysia and Singapore. The ability to use various applications and content creation for digital marketing is an obstacle for Bengkalis UMKM Community members. This is especially the case for the Baby boomers and Gen X people who were not familiar with communication technology such as smartphones at their young ages. Changes in consumers' purchasing patterns from offline to online provide challenges for MSME actors to master digital skills. Through community service, coaching and training were carried out for these business actors who become activity partners. The community service program aimed to provide knowledge and skills to Bengkalis MSME members to gain skills in digital marketing. This program was carried out through face-to-face and online meetings via zoom meetings so that participants can continue to be fostered for three months. Based on surveys to participants, it was found that this program increases the number of consumers on social media through the content they create during coaching. In addition, participants also managed to understand how to create good content to share on social media.